Functional Status of Thyroid Gland in Hospitalized Children With Downs Syndrome (Bangladesh Journal of Child Health, 2017)
Background: Over one-hundred and thirty years ago a link between Downs syndrome and thyroid disease had been proposed. The additive effects of this co-morbid condition leads to further amplification of the clinical problems in these children with Downs syndrome. While several international studies have shown association of thyroid dysfunction with Downs syndrome, there is paucity of available data from Bangladesh.Objective: The purpose of this study was to know the frequency of thyroid dysfunction in Downs syndrome children below the age of 12 years in our setting and to correlate the features of Downs syndrome with those of thyroid dysfunction.Methods: A cross-sectional study was carried out on 40 patients of Downs syndrome admitted at Dhaka Shishu Hospital from January 2014 to March 2015. Diagnosis of Downs syndrome was considered clinically with or without confirmation by karyotyping. Thyroid function was assessed by serum FT4 and TSH.Results: All 40 patients enrolled were below 5 years and most of them (72.5%) were within 12 months of age. Twenty-one cases were male and 19 were female. Hypothyroidism was found in 6 cases (15.0%), of which 4 (10.0%) had compensated hypothyroidism. Hyperthyroidism was not observed in any of the cases. There was no significant sex difference.Conclusion: Hypothyroidism was frequently associated in children with Downs syndrome in our setting. It thus seems necessary to screen all children of Downs syndrome for thyroid dysfunction.Bangladesh J Child Health 2015; VOL 39 (3) :123-128